Exploring the Most Promising Stem Cell Therapy in Liver Failure: A Systematic Review - Jeanne AdiwinataPawitan (Hindawi Limited, 2019)
Background. Alternative approaches to transplantation for liver failure are needed. One of the alternative approaches is stem cell therapy. However, stem cell therapy in liver failure is not standardized yet, as every centre have their own methods. This systematic review is aimed at compiling and analyzing the various studies that use stem cells to treat liver failure, to get an insight into potential protocols in terms of safety and efficacy by comparing them to controls. Methods. This systematic review was done according to PRISMA guidelines and submitted for registration in PROSPERO (registration number CRD42018106119). All published studies in PubMed/MEDLINE and Cochrane Library, using key words: "human" and "stem cell" AND "liver failure" on 16th June 2018, without time restriction. In addition, relevant articles that are found during full-text search were added. Inclusion criteria included all original articles on stem cell use in humans with liver failure. Data collected included study type, treatment and control number, severity of disease, concomitant therapy, type and source of cells, passage of cells, dose, administration route, repeats, and interval between repeats, outcomes, and adverse events compared to controls. Data were analyzed descriptively to determine the possible causes of adverse reactions, and which protocols gave a satisfactory outcome, in terms of safety and efficacy. Results. There were 25 original articles, i.e., eight case studies and 17 studies with controls. Conclusion. Among the various adult stem cells that were used in human studies, MSCs from the bone marrow or umbilical cord performed better compared to other types of adult stem cells, though no study showed a complete and sustainable performance in the outcome measures. Intravenous (IV) route was equal to invasive route. Fresh or cryopreserved, and autologous or allogeneic MSCs were equally beneficial; and giving too many cells via intraportal or the hepatic artery might be counterproductive.